Influence of age on speech-in-noise and spatial processing abilities in middle-aged adults - Pavithra Nayak; Suresh Pillai; Hari Prakash Palaniswamy (PLoS ONE, 2026)
Speech perception in noise (SPIN) difficulties are commonly associated with older adults, but emerging evidence suggests they may begin in midlife. This study investigated SPIN and spatial processing abilities in middle-aged adults using the Spatial Separation Sentence Test-Kannada (SSST-K). A cross-sectional design assessed 76 participants aged 41–60 years, divided into two groups (41–50 and 51–60 years). Assessments included: (1) the SSST-K to evaluate SPIN and spatial processing, (2) the Montreal Cognitive Assessment (MoCA) for general cognition, and (3) standardized questionnaires measuring noise exposure (NESI), physical activity (GPAQ), and mental status (PHQ-9). Hierarchical regression analysis revealed two key findings. First, in the co-located (0° azimuth) condition, cognition (MoCA) was the only significant predictor of SPIN performance, overshadowing age and other variables. Second, none of the tested variables predicted spatial advantage. Between-group comparisons showed no age-related differences in SPIN scores for the co-located condition, but the older subgroup (51–60 years) exhibited reduced spatial advantage and significantly lower MoCA scores. These results indicate that among the variables examined in middle-aged adults with self-reported normal hearing, cognitive function emerged as the strongest predictor of SPIN ability. However, the absence of audiometric verification, particularly extended high-frequency assessment, limits definitive conclusions about peripheral versus central contributions. The other variables, like noise exposure, mental health, and physical activity, had no significant influence. Future research with longitudinal designs and objective hearing assessment is needed to determine optimal ages and methods for SPIN screening in community and clinical settings.